Penggunaan Media Pembelajaran NHT Untuk Meningkatkan Hasil Pembelajaran Matematika Siswa Kelas 2 Di Tanjungsari Probolinggo - Aryawardana, Ludfi; ., Vifian Lestin Ferdina; ., Olik Susanti; ., Isa Romadani (CV. ITTC INDONESIA, 2022)
The Teaching Campus Program created by the Directorate General of Higher Education is an effort to improve the education system in Indonesia after the Covid-19 pandemic. In its implementation, students are assigned to target elementary schools with a focus on increasing understanding of literacy and numeracy which is applied to all subjects in elementary schools. One of the programs held by the researchers was to increase understanding of mathematics with material on multiplication arithmetic operations for students in class 2 of Tanjungsari Probolinggo Public Elementary School. The reason for choosing this class was because the average grade 2 math score was very low. To deal with these problems, the researcher used the Number Head Together cooperative learning model. In carrying out the research using the Classroom Action Research method with quantitative data analysis. The results of the research implementation showed that the NHT learning model was very effective in improving the learning outcomes of class 2 students at Tanjungsari Probolinggo Public Elementary School.